Mycoplasma detection in a mouse cell line and possible contamination source - Cornejo M., Willian (1992)
The detection of contaminating mycoplasma in a NS-1 myeloma celI line was studied comparing three methods The probable source of mycoplasma contamination were some batches of commercial sera Fetal Bovine Sera (FBS) mouse myeloma NS-1 cells and Vero celIs (African green monkey) were cultured on PPLO medium. The other methods involved the use of an indicator cell culture system (Vero cells) and the DNA-fluorochrome staining technique. The bacteriological procedure for the isolation of mycoplasma was successful with NS-l and Vero celIs, but not with FBS. However, mycoplasma colonies with typical "fried egg" appearance were only observed with Vero celIs. Moreover, the number of colonies isolated could be appreciated only after 18 days of growth. Vero tested, showed cytopathic effect (CPE). Initial1y, dark grasules appeared in the cytoplasm of the cells. At the 5th or 7th day, cell membranes showed small linger-like projections and vacuolization. By the 3rd or 4th week, the CPE was more pronounced. Monolayers of Vero cells were a1so grown on coverslips for 2 to 5 days and were stained with Hoechts DNA: fluorescent stain. The cells show discrete zones of fluorescence in the cytoplasm and nuclei. The: fluorescent spots were time-dependent Hoechst technique appears to be the method 01 choice, since it is more efficient, less time consuming and simpler.